Comparative analysis of first person shooter games on game modes and weapons – military-themed, overwatch, and player unknowns’ battleground - Hae Kyung Rhee; Doo Heon Song; Jeong Hoon Kim (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
First-person shooter is a video game genre centered on gun and other weapon-based combat in a first-person perspective. It is the second most favored genre among young Korean male gamers. Recently, the resurrected old-school-shooter Overwatch and Battle Royale style Player Unknowns’ Battleground enjoy a big success in  Korean game market and worldwide meanwhile the military-themed games in the genre have shrunken especially in Korean market. In this paper, we take a comparative analysis on the game structures and game modes and particularly the weapon system used in the game to facilitate the player balancing in the team based combat. Two recent successful games in the genre showed different strengths over traditional military-themed first-person-shooter in this comparative study.